Human Capital Perception in Hybrid Work Environments: A Qualitative Exploration of Artificial Intelligence Integration - Mejía Ochoa, Francisco Javier (American Journal of Business Science Philosophy, 2025)
Hybrid work environments that blend human labor with artificial intelligence (AI) systems reconceptualize assumptions about identity, agency, and value creation within the firm. Grounded in the philosophical postulate that organizational reality is a social construct, this study analyses how human capital interprets AI integration in companies located in the Sierra de Zongolica, Veracruz. A phenomenological design was employed; twenty-five semi structured interviews and two focus groups were conducted with service, production, and administrative workers who interact daily with human–AI systems. Thematic coding revealed four interrelated constructs: AI as an operational enabler, perceived occupational well-being, enhanced professional autonomy, and holistic job satisfaction. Participants reported that AI lightens repetitive tasks, shortens cycle times, and broadens decision-making scope, thereby reducing stress and improving work–life balance. Concurrently, concerns arose regarding the loss of human interaction and job stability, particularly among longer-tenured employees. The findings indicate that AI functions as a contingent complement to human expertise; its value depends on transparent algorithms, upskilling programmes differentiated by age cohorts, and change management sensitive to the cultural context. The study concludes that corporate strategies and public policies must align technological efficiency with ethical governance so that digital transformation simultaneously fosters productivity and human development.
Keywords: human capital; hybrid work; professional autonomy; artificial intelligence